Higher postpartum α-defensin secretion is associated with diet during pregnancy and lower intensity of negative maternal mood - Yu Shimizu; Yuki Yokoi; Shuya Ohira; Hirohisa Izumi; Satomi Kawakami; Fuka Tabata; Hirohiko Nakamura; Yasuhiro Takeda; Takashi Kimura; Koshi Nakamura; Akiko Tamakoshi; Tokiyoshi Ayabe; et al. (npj Women's Health, 2026)
Abstract Perinatal anxiety and depression are serious concerns for many mothers. However, current early-phase community-based care is not always sufficient to prevent their aggravation, necessitating self-care approaches through daily habits that lower social and psychological implementation barriers. α-Defensins secreted by small intestinal Paneth cells are known to affect mental state by modulating the intestinal microbiota, and dietary factors are associated with α-defensin secretion. Thus, we investigated the relationship between perinatal α-defensins (human defensin 5: HD5) and mood states, and explored dietary factors relating to HD5 secretion. In 48 mothers, higher fecal HD5 concentrations at 3-day postpartum were associated with lower intensity of negative mood states at 1-month postpartum. Higher HD5 correlated with characteristics of the intestinal microbiota related to lower intensity of negative mood. Furthermore, the intake of several nutrients during mid-pregnancy was associated with HD5. These findings may propose novel perspectives for promoting women’s health through dietary habits during pregnancy.